Quad-band terahertz metamaterial absorber using three parallel gold strips surrounded by two identical gold ring arcs. (8th February 2022) - Lai, Shengxiong; Xu, Wei; Yang, Zhuchuang; Lu, Liming; Wang, Kun; Feng, Sen; Zhang, Sijian; Wu, Yangkuan; Wang, Ben-Xin
Abstract: Quad-band terahertz metamaterial absorber with near-perfect absorption is given in this paper. It is designed by a patterned Au layer and a continuous Au film separated by an insulating dielectric layer, of which the patterned Au layer is consisted of three parallel Au strips (a longer and two shorter) surrounded by two Au ring arcs of the same size. Four separated terahertz absorption peaks with narrow bandwidths and large absorptance are realized. The first three absorption peaks are due to the fundamental modes of the Au strips and the Au ring arcs, while the fourth absorption peak is ascribed to the excitation of three-order resonance in the Au ring arcs. The field distributions of the four absorption peaks are presented to verify their physical mechanisms. The influence of geometrical dimensions of the proposed configuration on the performance of the quad-band light absorption is discussed. Moreover, considering the potential sensing applications, the sensing performance of the proposed absorption device is also explored. The suggested scheme could provide considerable application prospects in selective thermal radiation, spectral imaging, sensing, detecting, electromagnetic stealth, etc.